2022
DOI: 10.1155/2022/1059445
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Inflammatory Factors in Pediatric Appendicitis

Abstract: Background. The study analyzed gut microflora’s composition and investigated the associations between the associations between gut dysbiosis and inflammatory indicators in pediatric patients with acute appendicitis. Methods. High-throughput sequencing and bioinformatics analysis were used to investigate the composition and diversity of gut microflora in 20 pediatric patients with acute appendicitis and 11 healthy children. Endpoints measured were operational taxonomic units (OTU) of gut microflora. The OTU and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…In addition to obesity, there are other diseases that have been associated with pediatric gut dysbiosis that are also linked to the severity of COVID-19. For example, additional pulmonary complications that result in pneumonia in children infected with SARS-CoV-2 may also be associated with acute appendicitis, a condition associated with gut microbiome dysbiosis [104][105][106][107]. In acute myeloid leukemia (AML), a study demonstrated that the intensity of chemotherapy played a role in the immune response to COVID-19 and the severity of disease [108].…”
Section: Covid-19 Comorbidities Associated With Dysbiosis Imbalances ...mentioning
confidence: 99%
“…In addition to obesity, there are other diseases that have been associated with pediatric gut dysbiosis that are also linked to the severity of COVID-19. For example, additional pulmonary complications that result in pneumonia in children infected with SARS-CoV-2 may also be associated with acute appendicitis, a condition associated with gut microbiome dysbiosis [104][105][106][107]. In acute myeloid leukemia (AML), a study demonstrated that the intensity of chemotherapy played a role in the immune response to COVID-19 and the severity of disease [108].…”
Section: Covid-19 Comorbidities Associated With Dysbiosis Imbalances ...mentioning
confidence: 99%
“…In addition, the appendix has the highest concentration of gut-associated lymphoid tissue (GALT) and is considered important for the immune response of the gastrointestinal tract. Changes in the gut microbiota may have a direct effect on GALT in the appendix, leading to altered immune function [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Shi et al identified specific bacteria in the gut microbiota after appendectomy that may be involved in intestinal inflammation via induction of cellular immune responses, including induction of leukocyte chemotaxis and stimulation of proinflammatory cytokine production [ 34 ]. In addition, there is evidence that Clostridia are more abundant in individuals with acute appendicitis than in healthy controls [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Phascolarctobacterium has been reported to abundantly colonize the human gastrointestinal tract 56 and has been positively associated with autism spectrum disorder 57 and Alzheimer's disease. 58 Although less investigated, Megasphaera has been reported to increase in abundance after appendectomy in both children and adults, 33, 59 while it seems to be beneficial for those with diarrheal cryptosporidiosis. 60 Interestingly, we found that the galactose degradation I pathway (PWY-6317) was depleted in disease stages; therefore, it was selected as an important feature for the model classifying tumors.…”
Section: Discussionmentioning
confidence: 99%